Tumor glycolysis, an essential sweet tooth of tumor cells. (November 2022) - Paul, Sumana; Ghosh, Saikat; Kumar, Sushil
Abstract: Cancer cells undergo metabolic alterations to meet the immense demand for energy, building blocks, and redox potential. Tumors show glucose-avid and lactate-secreting behavior even in the presence of oxygen, a process known as aerobic glycolysis. Glycolysis is the backbone of cancer cell metabolism, and cancer cells have evolved various mechanisms to enhance it. Glucose metabolism is intertwined with other metabolic pathways, making cancer metabolism diverse and heterogeneous, where glycolysis plays a central role. Oncogenic signaling accelerates the metabolic activities of glycolytic enzymes, mainly by enhancing their expression or by post-translational modifications. Aerobic glycolysis ferments glucose into lactate which supports tumor growth and metastasis by various mechanisms. Herein, we focused on tumor glycolysis, especially its interactions with the pentose phosphate pathway, glutamine metabolism, one-carbon metabolism, and mitochondrial oxidation. Further, we describe the role and regulation of key glycolytic enzymes in cancer. We summarize the role of lactate, an end product of glycolysis, in tumor growth, and the metabolic adaptations during metastasis. Lastly, we briefly discuss limitations and future directions to improve our understanding of glucose metabolism in cancer.